An Analysis of Writing Tasks in English Textbook for Office Administration Students entitled Bahasa Inggris SMA/MA/SMK/MAK Kelas XI - Siti Maryam Solihat (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2021)
Vocational High School students majoring in Office Administration will be required to do writing tasks when they work in companies after graduating from school. This study aimed at finding out the appropriateness of writing tasks in English textbook entitled Bahasa Inggris SMA/MA/SMK/MAK Kelas XI for Office Administration students at Eleventh Grade. Content analysis method was employed in this study and the analysis was based on Nunan’s (2004) theory of task components (goal, input, procedure) and Hyland’s (2003) theory of writing procedures (graphology, scaffolding, composing). The results indicated that the textbook is inappropriate for Office Administration students. Among the three components of writing task, writing goals and texts (input) in the analyzed textbook do not correspond to the ones required by Office Administration students. The goals and input in the textbook are related to daily life situations, while the students are supposed to write business documents. In terms of procedure, the textbook leaves out graphology tasks and only provides the tasks for scaffolding and composing. Scaffolding has four categories: language familiarization (found in Chapter 1, 2, 5, 6), model analysis and manipulation (not found in any chapters), controlled composition based on model (found in Chapter 1, 2, 3, 4, 5, 6, 8), guided composition (found in Chapter 2, 3, 5, 6, 7, 8). Then, composing has two categories: composition heuristics (found in Chapter 4 and 8) and extended writing (found in Chapter 3 and 5). These findings imply that the needs arise to select more relevant writing tasks for Office Administration students or design new writing materials for the students.